A rare case of non-functional Paraganglioma of urinary bladder with No LUTS - Mohammad Poury; Mohsen Ayati; Seyed Ali Momeni; Laleh Sharifi (Urology Case Reports)
Paraganglioma originates from chromaffin cells of the sympathetic nervous system. Paraganglioma of urinary bladder are very rare tumors that arise from the ganglion cells and usually mistakenly have been diagnosed and treated because of its rarity and diverse symptoms. Here, we present our patient with incidental finding of non-functional paraganglioma of urinary bladder who showed no lower urinary tract symptoms (LUTS). Timely diagnosis, treatment, and postoperative reviews are in effect for management of these patients.